Elevated vitamin E content improves all-trans β-carotene accumulation and stability in biofortified sorghum - Che, Ping (Proc Natl Acad Sci U S A, 2016)
Micronutrient deficiencies are common in locales where people must rely upon sorghum as their staple diet. Sorghum grain is seriously deficient in provitamin A (β-carotene) and in the bioavailability of iron and zinc. Biofortification is a process to improve crops for one or more micronutrient deficiencies. We have developed sorghum with increased β-carotene accumulation that will alleviate vitamin A deficiency among people who rely on sorghum as their dietary staple. However, subsequent β-carotene instability during storage negatively affects the full utilization of this essential micronutrient. We determined that oxidation is the main factor causing β-carotene degradation under ambient conditions. We further demonstrated that coexpression of homogentisate geranylgeranyl transferase (HGGT), stacked with carotenoid biosynthesis genes, can mitigate β-carotene oxidative degradation, resulting in increased β-carotene accumulation and stability. A kinetic study of β-carotene degradation showed that the half-life of β-carotene is extended from less than 4 wk to 10 wk on average with HGGT coexpression.